Recombinant human thrombopoietin as a novel platelet-driven regulator accelerating hepatic regeneration in acute liver failure - Shen, Yunzhi; Han, Fengzheng; Wang, Tao; Jing, Li; Luo, Ying; Ha, Fushuang; Lu, Yongping; Liang, Jing (Frontiers in Pharmacology, 2026)
ObjectiveThe aim of this study is to investigate the effect of recombinant human thrombopoietin (rhTPO) on liver regeneration in rats with acute liver failure (ALF) induced by D-galactosamine (D-GalN).MethodsSixty-six rats were divided into a control group and a TPO group. The control group received daily injections of normal saline, while the TPO group received daily injections of rhTPO. After five consecutive days of treatment, an ALF model was established in all rats via D-GalN administration. Survival status of the two groups was observed. Platelet count (PLT), liver function indicators, hepatocyte growth factor (HGF), and liver regeneration-related indicators were measured at different time points. Additionally, transcriptomic and proteomic analyses were performed on liver tissues.ResultsCompared with the control group, the TPO group showed significantly higher levels of PLT, serum TPO, and HGF, milder liver tissue necrosis, a higher liver weight index, lower levels of alanine aminotransferase (ALT) and total bilirubin (TBil), and stronger liver regeneration capacity (as indicated by Ki67 and BrdU indices). Combined transcriptomic and proteomic analyses revealed that the expression of genes related to cell proliferation signaling pathways, such as Mapk1 and Map2k1, was significantly increased, while the expression of genes related to inflammatory pathways was significantly decreased.ConclusionrhTPO can promote the recovery of liver function and enhance liver regeneration in ALF rats by increasing PLT, stimulating cell proliferation, and inhibiting inflammation.